2019
DOI: 10.1108/whatt-04-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

The emerging importance of risk management and enterprise risk management strategies in the Indian hospitality industry

Abstract: Purpose The purpose of this paper is to discuss the outlook for risk management and enterprise risk management (ERM) within the hospitality sector including how ERM is being balanced with the need to innovate, and what boards of directors are doing to become more engaged in risk oversight. The implementation of ERM is about taking a strategic view of risk and linking it to business goals and value creation. Design/methodology/approach An interviewer-administered survey was used to collect data from 33 senior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 15 publications
0
19
0
2
Order By: Relevance
“…Thus, the company can change the configuration of its assets so that they can be adjusted to changes in the environment (Mishra et al, 2019). Another study is research conducted by Vij (2019). Vij (2019) tries to examine the impact of implementing ERM on the innovation ability of companies in the Indian hospitality sector.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the company can change the configuration of its assets so that they can be adjusted to changes in the environment (Mishra et al, 2019). Another study is research conducted by Vij (2019). Vij (2019) tries to examine the impact of implementing ERM on the innovation ability of companies in the Indian hospitality sector.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Another study is research conducted by Vij (2019). Vij (2019) tries to examine the impact of implementing ERM on the innovation ability of companies in the Indian hospitality sector. From the results of his survey, Vij (2019) concluded that the application of ERM in the hospitality sector can connect risk with organizational goals so that it can balance innovation and risk.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this reality, it is important to understand the different kinds of risk and the perceptions and likely responses of senior management as well as the action that can be taken to mitigate the underlying issues. These considerations are very relevant to industry and they are addressed by Vij (2019) in her paper that examines the perspectives of senior risk professionals in relation to risk management and enterprise risk management in the Indian hospitality sector.…”
Section: Risk Management and Enterprise Risk Management Strategiesmentioning
confidence: 99%
“…The emerging importance of risk management and enterprise risk management strategies Given that the tourism and hospitality industry is dynamic in nature, any disruptive innovation is likely to cause vulnerability to changes occurring in both internal and external environments. Vij (2019) conducted a study to determine senior management perspectives on risk management and enterprise risk management (ERM) in the hospitality sector. ERM is essentially concerned with a strategic view of risk and relating it to business goals and value creation for the organization.…”
Section: Business Model Innovations In the Indian Hospitality Industry: Consideration Of Outsourcing Specialty Restaurantsmentioning
confidence: 99%